STUDY OF NATURAL DYE-YIELDING PLANTS WITH ITS MEDICINAL VALUE IN DISTRICT RAJGARH (M.P.) - Khan, Ajra; BalaSanghi, Shail (International Journal of Research -GRANTHAALAYAH, 2016)
The present paper is based on extensive survey. Collection of ethnobotanical information and natural dye yielding plants Rajgarh District (M.P.). The study reports 15 natural dye yielding plant species belong to 13 families. Along with their botanical name, local name, family, habit, dye yielding plant parts used are mentioned in the paper. Apart from, medicinal uses, it also describes preparation of dyeing stuff. Use of mordant’s and specific dye utilization to serve various purposes, including several of the new dye resources.